2008
DOI: 10.1074/jbc.m707710200
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Binding to γA/γ′-Fibrin Engages Both Exosites of Thrombin and Protects It from Inhibition by the Antithrombin-Heparin Complex

Abstract: Thrombin exosite 1 binds the predominant ␥ A /␥ A -fibrin form with low affinity. A subpopulation of fibrin molecules, ␥ A /␥-fibrin, has an extended COOH terminus ␥-chain that binds exosite 2 of thrombin. Bivalent binding to ␥ A /␥-fibrin increases the affinity of thrombin 10-fold, as determined by surface plasmon resonance. Because of its higher affinity, thrombin dissociates 7-fold more slowly from ␥ A /␥-fibrin clots than from ␥ A /␥ A -fibrin clots. After 24 h of washing, however, both ␥ A /␥-and ␥ A /␥ A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
109
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 46 publications
13
109
0
Order By: Relevance
“…Thrombin bound to fibrin was shown to remain functionally active. 32 Despite the higher affinity to ␥A/␥Ј fibrin, the release of FpA from ␥A/␥Ј fibrinogen by thrombin was similar compared with ␥A/␥A fibrin, 32 a finding supported by our data. 33 In addition, Fredenburgh et al 32 showed that binding of thrombin to the ␥Ј chain offers thrombin protection from inhibition by heparin in complex with heparin cofactor II or antithrombin, confirming a previous report by Pospisil et al 34 As exosite II provides the site of interaction for both heparin and the ␥Ј chain, it is probable that competitive inhibition for exosite II plays a role in the mechanism underpinning this.…”
Section: Thrombin Bindingsupporting
confidence: 80%
See 1 more Smart Citation
“…Thrombin bound to fibrin was shown to remain functionally active. 32 Despite the higher affinity to ␥A/␥Ј fibrin, the release of FpA from ␥A/␥Ј fibrinogen by thrombin was similar compared with ␥A/␥A fibrin, 32 a finding supported by our data. 33 In addition, Fredenburgh et al 32 showed that binding of thrombin to the ␥Ј chain offers thrombin protection from inhibition by heparin in complex with heparin cofactor II or antithrombin, confirming a previous report by Pospisil et al 34 As exosite II provides the site of interaction for both heparin and the ␥Ј chain, it is probable that competitive inhibition for exosite II plays a role in the mechanism underpinning this.…”
Section: Thrombin Bindingsupporting
confidence: 80%
“…32 Despite the higher affinity to ␥A/␥Ј fibrin, the release of FpA from ␥A/␥Ј fibrinogen by thrombin was similar compared with ␥A/␥A fibrin, 32 a finding supported by our data. 33 In addition, Fredenburgh et al 32 showed that binding of thrombin to the ␥Ј chain offers thrombin protection from inhibition by heparin in complex with heparin cofactor II or antithrombin, confirming a previous report by Pospisil et al 34 As exosite II provides the site of interaction for both heparin and the ␥Ј chain, it is probable that competitive inhibition for exosite II plays a role in the mechanism underpinning this. 21,35,36 So although on one hand the ␥Ј chain is responsible for antithrombin I activity and reduction of intrinsic activation, FpA release on the other hand is normal and thrombin is afforded protection against serpin inactivation in the presence of glycosaminoglycans.…”
Section: Thrombin Bindingsupporting
confidence: 80%
“…Fibrinogen and fibrinogen fragment X were prepared and characterized as described (13)(14)(15). Human antithrombin was from Affinity Biologicals, Inc. (Ancaster, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Platelets are major players of arterial thrombus formation, as also demonstrated by the clinical efficacy of anti-platelet agents in cardiovascular prevention. The fibrinogen ␥Ј chain, through its ability to bind to thrombin, might enhance the amount of clot-bound thrombin, known to be active in the presence of the heparin-antithrombin complex, and thus scarcely inactivated by traditional anticoagulants (heparins, indirect Factor Xa inhibitors) (3). Thus, clot-bound, active thrombin may represent a storage pool of the enzyme, facilitating arterial thrombus formation and growth.…”
mentioning
confidence: 99%
“…fibrin, binds with a considerable specificity thrombin, so that in the early studies fibrin was termed antithrombin I (2). Thrombin has a divalent interaction with two classes of binding sites on fibrin, one of low affinity in the E domain and the other of high affinity in the D domain of fibrin(ogen) molecules (3). Binding of thrombin to fibrinogen involves sequences of both A␣ and B␤ chain, which contain recognition sites in the fibrinogen E domain.…”
mentioning
confidence: 99%